Optimizing the Role of Women Through Fish Waste Management into Fish Crackers as an Effort to Alleviate Poverty in Tanjungbalai City - Dedeng irawan; Asrul Siregar; Ihsan Rambe; Arief Hidayat; Frans Sahputra Silitonga (Outline Publisher, 2026)
The high level of fishing activity in Tanjungbalai City produces fish processing waste that is not optimally utilized and has the potential to pollute the environment. Furthermore, poverty and low incomes among fishing families remain major challenges, particularly for women (housewives) who lack independent incomes. This Community Service Program aims to optimize the role of women through training and mentoring in processing fish waste into high-value fish crackers. This program aims to improve the skills of housewives, create family economic independence, and reduce environmental waste in coastal areas. Implementation methods include nutrition and hygiene counseling, technical training in making fish crackers from waste diversification, assistance with attractive packaging, and education on digital marketing and simple financial management. The program results in improved skills and creativity among participants in processing fish waste, the creation of hygienic processed products, and the enhancement of the capacity of new entrepreneurs. Thus, fish waste management is not only effective in preserving the coastal environment but also serves as a significant alternative source of income to alleviate poverty and improve family welfare in Tanjungbalai City.